The Revival of Islamic Traditional Medical Method Among Muslim Society During Covid-19 Pandemic - Ihsan Kamaludin; Fany N. R. Hakim; Shifa Nisrina S (Ulumuna, 2022)
The Covid-19 Pandemic does not only affect the social life but also encourages many Muslim communities to find alternative solutions to maintain the immunity of their bodies. Consuming herbal medicines and conducting some Islamic traditional medical methods are currently back into a social trend because some people believe that the methods can ward off all forms of the disease. The focus of this research is the implementation of traditional Islamic medicine methods in West Java and aims to understand thoroughly the impact of the use of alternative medical methods in the society. This qualitative study with a field analysis approach employed observations and interviews to collect the required data. The findings show that the use of herbal medicine and traditional Islamic healing methods during Covid-19 pandemic become a new trend since people try to seek alternative ways to maintain their immunity. The religious foundation plays an important role in this situation since people find out that Islam is not only about worship but also health management; in this case, many people try to use the religious-based healing methods.